Hate Speech of X (Twitter) Users Towards Two Foreign Celebrities - Ramadhani, Aulia Maghfirah; Sunra, La; Mustikawati, Yunitari (State University of Makassar, 2024)
Speaking is a way to communicate. Speaking can be done to express various opinion, such as praising someone, expressing thiughts, or even offending someone intentionally. Hate speech is also a delibrate offense to someone’s feelings. In hate speech, someone can be insulted, made fun of, or laughed at, which can create a bad impression on the listener. The purpose of this study is to categorize hate speech phrases and the strategies of those who write their hate expression. This research used qualitative method. Hate speech of (X) Twitter users towards two feoreign celebrities was the subject of the study. The comments left on the @Popbase pages were the source of the research of the research data. The data set consist of comments containing hate speech. The data analysis technique used in this research involves used the Mondal et al. (2017) theory to identify types of hate speech and the Culpeper (1996) theory to explain the strategies of hate speech. The findings of this research are as follows: (1) there six types of hate speech found in this study with the most common types being behavior and physical and followed by race, sexual orientation, disabilities, and gender, and (2) there are 4 strategies used by X (Twitter) users, namely negative impoliteness, bald on record, positive impoliteness and sarcasm or mock politeness, ranked from highest to lowest frequency. Keyword: Hate speech, Selena Gomez, Harry Styles, Categories of Hate Speech, Twitter (X)